Representação da informação de Blockchains: uma aproximação com o domínio dos metadados arquivísticos - GONÇALVES, Nadynne Cristinne da Silva (2022)
In Archival Science, the use of metadata applied to documents can be observed in archival representation activities that involve the processes of classification and description. This latter is understood as the activity of describing archival material through attributes that characterize it. The activity requires attention mainly in the digital environment, where there is a considerable accumulation of documents and the emergence of technologies to assist in records management, such as the Blockchain. Outside the financial environment, this technology is normally used for document authentication, generating representational data from these documents in its registration base. This research aims to analyze the capacity of Blockchain.com website description units to record archival metadata. The method adopted was the analysis of the access points of blocks, transactions and addresses on the website, to verify the possibility of parity between the attributes of the Blockchain.com units and the elements of the standards ABNT ISO 23081-2, ISAD(G) and ISAAR(CPF). Through the research it was possible to verify that, despite not following archival representation standards, the data from the website units have similarities with the standards, especially with ABNT ISO 23081-2, providing to the users with structured, contextualized and understandable information.